Which plumage patches provide information about condition and success in a female fairy-wren?. (21st November 2022) - Nolazco, Sergio; Delhey, Kaspar; Fan, Marie; Hall, Michelle L; Kingma, Sjouke A; Roast, Michael J; Teunissen, Niki; Peters, Anne
Abstract: Recent evidence suggests that female ornaments can commonly act as signals. However, how signaling functions might be affected by the tendency for reduced ornament elaboration in relation to males is less well-understood. We address this in mutually ornamented purple-crowned fairy-wrens. We investigated putatively ornamental (tail, ear coverts, crown) and non-ornamental (throat, back) plumage patches in females and compared our findings to previous studies in males. Both sexes have brown backs, buff-white throats, and turquoise-blue tails (bluer in males), while ear coverts are rufous in females and black in males. Both sexes also have a seasonal crown (slate-gray in females, black-and-purple in males). Dominant (breeder) females expressed more complete and grayer (more ornamented) crowns, although variation in coloration should not be discriminable by individuals. Unexpectedly, subordinates showed more colorful (saturated) rufous ear coverts, which should be discriminable. Condition-dependence was only evident for crown completeness (% slate-gray cover). Females with more reddish-brown backs were more reproductively successful. Variation in plumage characteristics did not explain differential allocation by mates or chances of gaining dominance. Our outcomes were not entirely consistent with findings in males. The most notable disparity was for the crown, a signal used in male-male competition that in females seems to be expressed as an incomplete version of the male crown that is not associated with fitness benefits. Our study shows that in a species, multiple traits can vary in their information content and that female ornaments can sometimes be less informative than in males, even those that are produced seasonally. Abstract : Female "decorations" (ornaments) are often less elaborate than those of males, but whether and how this affects ornament function is not clear. We investigate condition dependence and associations with fitness for multiple plumage patches in female purple-crowned fairy-wrens, some ornamental, some cryptic. Unlike previous studies in conspecific males, we found no evidence for fitness benefits associated with the female ornaments. Our study suggests that ornaments in females can be less informative than in males.